Environment, health, and population displacement : development and change in Mozambique's diarrhoreal disease ecology - Collins, Andrew E. (Routledge revivals., 2018)
First published in 1998, this book contributes to our understanding of emergent and resurgent infectious diseases and health ecology in developing areas through detailed spatial and temporal analysis of recent cholera and bacillary dysentery epidemics in Mozambique. The book examines the influence of environmental, demographic and socio-economic changes on the nature and context of cholera and bacillary dysentery. It provides a detailed background to the two diseases based on their ecology and contemporary status in human communities together with analysis of extensive primary field data centered on three key urban areas in central Mozambique. Influences are weighed up against factors relating to the individual ecologies of the different pathogens, primary subsistence, and the impacts of Mozambique's history of conflict and development policies on human vulnerability. The extensive case study material is used to provide clear indications of appropriate ways forward in the field of environmental health management.